ANALISIS BIAYA STANDAR DALAM MENENTUKAN HARGA POKOK PRODUKSI STONEWARE BERBAHAN BAKU UTAMA LEMPUNG KALIMANTAN DAN MANFAATNYA BAGI KEPUTUSAN BISNIS PADA UPT PSTKP BALI – BPPT - I Nyoman Normal; WIRYAWAN SUPUTRA GUMI (Forum Manajemen STIMI Handayani Denpasar, 2012)
Standard costing is predetermine cost which must expenditured to produceunit product or to paid special operation. Standard cost systems was design to costcontrol, be important tool to evaluate judgement that was setting. The aims of thisresearch were : (1) To knew cost of good manufactured stoneware that main rawmaterial of kalimantan blend by standard cost systems; and (2) To knew usefull ofstandard costing for business decision. The research results shew that : (1) Costof good manufactured stoneware that main raw material of kalimantan blend bystandard cost systems was various base on the composition use. The smallest costof good manufactured stoneware was XID composition about Rp 1.628,02 each kgand the biggest was FRC-1 composition about Rp 2.028,68 each kg. Cost of goodmanufactured stoneware by the standard cost systems was bigger than actual costsystems, because there were different into computation ways of raw material, differentloading of direct labour cost, and different loading of manufacturing overhead cost,except the XID composition was smaller; (2) Standard cost application is very usefulinto business decision making for stoneware product, that is : a) As a tool of control,b) As a tool of decision making, c) As a tool of rational cost measurement, and d) Asa tool of recording cost economizing.